Disleksia dan Metode Penanganannya dalam Film Taare Zameen Par (Sebuah Tinjauan Psikolinguistik) - Pramudita Septiani; Tia Pratiwi; Triana Ulfah; Sumarlam Sumarlam (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
This study discusses how the method of handling the type of dyslexic language acquisition inability in Taare Zameen film Par. Dyslexia is one type of learning difficulties in children, namely reading disability. The method used in this study is a descriptive method with the presentation of data from research results presented through words. The discussion presented includes (1) the characteristics of dyslexia; (2) learning solutions to the type of dyslexia; (3) solutions to the treatment of dyslexia. The results obtained in this study show that dyslexia can be treated using multisensory methods. The multisensory method utilizes visual abilities or students' visual abilities and kinesic hearing abilities at this level, namely awareness of movement and touch on students. Thus this method can assist in the implementation of learning for dyslexic children and in the future there will no longer be dyslexic children who are unable to write, read, and count. This study discusses how the method of handling the type of dyslexic language acquisition inability in Taare Zameen film Par. Dyslexia is one type of learning difficulties in children, namely reading disability. The method used in this study is a descriptive method with the presentation of data from research results presented through words. The discussion presented includes (1) the characteristics of dyslexia; (2) learning solutions to the type of dyslexia; (3) solutions to the treatment of dyslexia. The results obtained in this study show that dyslexia can be treated using multisensory methods. The multisensory method utilizes visual abilities or students' visual abilities and kinesic hearing abilities at this level, namely awareness of movement and touch on students. Thus this method can assist in the implementation of learning for dyslexic children and in the future there will no longer be dyslexic children who are unable to write, read, and count.